PSYCHOBIOLOGICAL PREDICTORS OF EMOTIONAL INTEGRITY IN SOCCER PLAYERS - SAHA SRILEKHA; SAHA, SOUMENDRA (International Journal of Pharma and Bio Sciences, 2015)
Purpose of this study was to identify the relationships between different emotional feelings; mood states and associated psychobiological changes pertaining to inner emotional core of promising soccer players of Malaysia. One-hundred and eighteen young male soccer players were recruited on the basis of selection criteria as participants, who were subjected to evaluation of projective analyses of emotionality (in the form of index of emotional integrity); mood states and inner psychobiological status (autonomic indices of habituation paradigm skin conductance response components). Outcomes of multiple linear regression analyses revealed predictive relationships between differential mood variations, the psychobiological and inner core of emotional integrity. Skin conductance indices, such as - tonic component of spontaneous fluctuation (SF) or non-specific skin conductance response (NS-SCR) and phasic component of skin conductance responses such as – amplitude and autonomic recovery were observed to contribute onto the changes observed in the extent of emotional integrity revealed by projective analyses of emotional factor responses. Decomposition of autonomic skin conductance phasic activity indices evidentially substantiated changes in innate psychological make-up, which however was observed to explain affective-motivational aspects of soccer performers.